Corneal endothelial cell morphology of normal dogs in different ages - Rodrigues, G. N.; Laus, J. L.; Santos, J. M.; Rigueiro, M. P.; Smith, R. L. (Blackwell Publishing, 2006)
Endothelial cell function is essential to maintain corneal transparency, but unfortunately the regenerative capacity of the endothelium is limited. There are only a few reports describing the effect of age on morphologic appearance of corneal endothelial cells of dogs. Studies of normal corneal endothelial cells in humans and dogs have shown a decrease in endothelial cell density (ECD) and an increase in pleomorphism and polymegethism with advancing age. The purpose of this study was to investigate the effect of age on ECD and endothelial cell morphology in dogs. A total of 30 dogs were divided into three groups (10 dogs/group) based on age: group 1 (2-12 months old), group 2 (24-72 months old), and group 3 (84 months or older). Corneas were processed for light and scanning electron microscopy. Results showed only difference in cell density between group 1 and groups 2 and 3, showing an initial decrease in cell density as the animal matured. Whereas there was significantly greater variation in cell size within the dogs in group 3 than there was within the other two groups, suggesting that there was increased polymegethism and pleomorphism with advancing age.
Keywords: corneal endothelium; dog; morphology; morphometry; scanning electron microscopy